ANALISIS DETERMINAN FAKTOR SISA HASIL USAHA PADA KOPERASI DI KOTA TEBING TINGGI - Daniel Situmorang; Rahima Br. Purba; Renny Maisyarah Maisyarah (Transpublika Publisher, 2024)
The aim of this research is to determine the influence of own capital, outside capital and business volume partially and simultaneously on the remaining business results in cooperatives in Tebing Tinggi City from 2018-2022. The research method used is quantitative. In this research, the data analysis technique used is statistical analysis using SPSS software. The results of partial hypothesis testing, own capital has a significant effect on the remaining business results in Cooperatives in Tebing Tinggi City for the 2018-2022 period, external capital has a significant effect on the remaining business results of Cooperatives in Tebing Tinggi City for the 2018-2022 period, business volume has an effect significant impact on the remaining business results of cooperatives in Tebing Tinggi City for the 2018-2022 period. Simultaneously, own capital, outside capital and business volume have a significant effect on the remaining business results of cooperatives in Tebing Tinggi City for the 2018-2022 period.